Students' Error in Writing Descriptive Text Viewed from Surface Strategy Taxonomy - Ni Wayan Diani; Olga Dona Retsi; Novika Amalia; Maria Arina Luardini (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This study aimed to identify and explain the types of errors as well as to investigate the underlying causes of errors in writing descriptive texts among students of English Education Study Program at Universitas Palangka Raya. The study employed a qualitative descriptive method, the researcher described factual findings and aspects related to students’ errors in composing descriptive texts. The participants consisted of 30 second semester students from class C of intermediate English writing course. This study conducted an essay test to collect students’ writing in processing data. The results of students’ writing were then classified into types of errors based on the surface strategy taxonomy by Dulay, Burt and Krashen (1982). Furthermore, the researcher interviewed 5 students with more error categories than others to find out the causes of errors made by students. The results showed that students still made many errors in writing descriptive texts. There are 128 total errors found in the use of grammar in writing descriptive texts. The errors are: (1) omission which is 33 errors. (2) addition which is 23 errors. (3) misformation, 72 errors. The researcher did not find misordering errors in the students’ descriptive text writing. And based on interviews from 5 students, the cause of this error was lack of vocabulary size, time limitation, lack of comprehension, lack of confidence.